Molecular epidemiology of penicillinase-producing Neisseria gonorrhoeae isolates in France. (December 2017) - Micaëlo, M.; Goubard, A.; La Ruche, G.; Denamur, E.; Tenaillon, O.; Cambau, E.; Jacquier, H.; Bercot, B.
Abstract: Objectives: Characterizing the molecular epidemiology of antibiotic resistance is crucial for a better understanding of the evolution and spread of resistance in Neisseria gonorrhoeae . Here, we examine the molecular epidemiology of penicillinase-producing N. gonorrhoeae (PPNG) isolates in France. Methods: We investigated 176 PPNG isolates collected between 2010 and 2012 by the National Reference Centre in France. Genotyping was performed using the NG-MAST technique, bla TEM genes were Sanger-sequenced, and plasmids were characterized by PCR-typing. Results: We revealed the existence of four major clusters representing about one-third of PPNG circulating in France. These clusters were related to ST1479 (18/176, 10.2%), to ST1582 (15/176, 8.5%), to ST8922 (10/176, 5.6%), and to ST1285 (9/176, 5.1%). Wild-type TEM-1 was identified in 151 (151/176, 85.8%) PPNG isolates, and TEM-1 variants were mostly represented by the M182T mutation (14/176, 8%), followed by P14S/L (8/176, 4.5%), G228S (2/176, 1.1%), and Q269K (1/176, 0.6%). The bla TEM genes were carried by African (157/176, 89.2%), Asian (13/176, 7.4%), and Toronto/Rio (6/176, 3.4%) plasmids. The M182T variants were found in various genetic backgrounds, whereas the P14S variants were disseminated clonally. The G228S and Q269K variants belong to one of the four major clusters of PPNG, which suggests a recent de novo emergence of these mutations. Conclusions: Our results show that approximately one-third of the penicillinase-producing N. gonorrhoeae isolates in France belong to one of four major clusters and that the spread of the different TEM variants is associated with distinct patterns of molecular epidemiology.